S130 Exogenous Macrophages Are Retained in Mouse Lungs After Injury and Target Therapeutic Transgenes to the Injured Lung Parenchyma. (19th November 2012) - McNulty, K; Sage, EK; Alexander, R; Scotton, CJ; Janes, SM
Abstract : Introduction: Pulmonary fibrosis evolves in response to epithelial injury in a number of lung diseases, and carries a poor prognosis; novel therapies are urgently needed. The epithelial mitogen keratinocyte growth factor (KGF) has been shown to prevent fibrosis in a number of animal models however its therapeutic utility is limited by its short half-life. There is a growing interest in cell therapy approaches, and we hypothesised that macrophages could be used as vehicles to target KGF therapy to injured lung. Methods: Lentiviral vectors expressing luciferase, KGF and GFP (control) were generated and used to transduce the IC-21 macrophage cell line. Appropriate transgene expression was confirmed. KGF macrophages were co-cultured with primary mouse tracheal epithelial cells in a proliferation bioassay. Luciferase-expressing macrophages were tracked longitudinally using bioluminescence imaging after oropharyngeal delivery to the lungs of mice given bleomycin to induce injury, or saline control. Immunostaining was used to localise macrophages within lung sections. KGF and GFP-macrophages were delivered during bleomycin-induced lung injury; endpoint measures included lung histology, micro-CT analysis, and quantification of inflammatory cell infiltrates, vascular leak, lung collagen by HPLC, and inflammatory and fibrotic mediators by ELISA and qPCR. Results: Exogenously delivered macrophages were retained in the lungs of bleomycin-injured mice, but not uninjured controls, when given during either the inflammatory or fibrotic phases of injury, and localised to injured lung parenchyma. KGF-transduced macrophages induced proliferation of mouse tracheal epithelial cells during co-culture, but delivery to bleomycin-injured mice was not associated with overall improvements in endpoints when delivered during either the inflammatory or fibrotic phases of injury. Delivery of macrophages per se was associated with an increase in inflammatory mediators consistent with classical M1 macrophage activation, which may have off-set any beneficial effects of KGF-transduced macrophages. Conclusions: Exogenously delivered macrophages are preferentially retained in injured lung and show potential as vehicles to target therapeutic transgenes by localising to damaged areas. Whilst KGF-transduced macrophages induced epithelial proliferation in vitro, any protective effects in vivo may have been negated by the exacerbatory effects of macrophage delivery. Future work will determine whether ex vivo manipulation of macrophage phenotype can confer therapeutic benefit.